Structural and Energetic Compatibility: The Driving Principles of Molecular Evolution - Šponer, Judit E; Šponer, Jiří; Di Mauro, Ernesto (Astrobiology, 2019)
In this work, we provide an answer to the question formulated by Albert Eschenmoser: "How would you envisage the bridge between potentially primordial geochemistry that had been disordered and one that gradually became self-organizing?" Analysis of the free-energy profiles of some of the key reactions leading to formation of nucleotides and their oligomers shows that, whereas the first part of the pathway, up to nucleotides, is energy-driven, in the second low-energy part entropic control in the form of structural compatibility becomes more important. We suggest that the birth of modern metabolism requires structural compatibility, which is enabled by the commensurability of the thermodynamics of the synthetic steps with the stabilizing effect of those intermolecular interactions that play a key role in dictating entropic control of these reactions.
Keywords: Origin of Life; termodynamika; Prebiotic synthesis.; Self-organization; molekulární evoluce; Evolution, Molecular; Crystallization; Molecular evolution; Kinetics; krystalizace; Thermodynamics; původ života